Outcome of patients aged 80 years or older treated for chronic lymphocytic leukaemia. (21st November 2018) - Al‐Sawaf, Othman; Bahlo, Jasmin; Robrecht, Sandra; Fischer, Kirsten; Herling, Carmen D.; Hoechstetter, Manuela; Fink, Anna‐Maria; von Tresckow, Julia; Langerbeins, Petra; Cramer, Paula; Stilgenbauer, Stephan; Wendtner, Clemens M.; et al.
Summary: Clinical management of chronic lymphocytic leukaemia (CLL) in patients aged ≥80 years is based on limited evidence due to the lack of published information. Therefore, we analysed CLL patients aged ≥80 years using data from seven phase III clinical trials of the German CLL Study Group. Among 3552 participants, 152 were ≥80 years old at initiation of first‐line study treatment. Median age was 82 years (range 80–90). Concomitant diseases were present in 99% of the patients, with a median cumulative illness rating scale score of 8 (0–18). Chemoimmunotherapy with chlorambucil‐obinutuzumab (CLB‐OB) or chlorambucil‐rituximab (CLB‐R) was administered to 61 (40%) and 56 (37%) patients. The remaining patients received CLB ( n  = 19) or fludarabine (F, n  = 10), F/cyclophosphamide (FC, n  = 1), FC/rituximab (FCR, n  = 2) or bendamustine/rituximab (BR, n  = 3). Rates of grade 3 or 4 neutropenia and infections were 35% and 13%. Overall response rate was 77% with 13% complete remissions. Median progression‐free survival and treatment‐free survival were 17·2 and 32·3 months, respectively. Median overall survival was 48·3 months; adverse events (22%) and progressive CLL (16·4%) were the most frequent causes of death. These findings suggest that anti‐leukaemic treatment including chemoimmunotherapy is feasible and efficacious in ≥80‐year‐old CLL patients. However, this group of patients lives for a shorter time than age‐matched controls of the general population.